A Study Questioning Strategies in the Interview Discourse of Kanchai Kamnerdploy in the Talk show “Hone-Krasae” - Pakinsee, Prapasiri; Waraseeha, Kanokkarn (Journal of Humanities and Social Sciences Loei Rajabhat University, 2023)
This research aims at studying of questioning strategies in the interview discourse of Kanchai Kamnerdploy in the talk show, “Hone-Krasae” The researcher study the retrospective tape from the YouTube website, “Hone-Krasae” (Hone-Krasae) Official that aired between May - July 2021, and selected only tapes which have 1 million views or more. (Refer to information as on September 2, 2021), there were 14 episodes of the interview in talk shows “Hone-Krasae”. The results revealed that Kanchai Kamnerdploy chose various questioning strategies in the interview discourse of the talk show, “Hone-Krasae”, asking for the information needed from the interview. The results revealed that the 9 questioning strategies are: 1) repeating a question, 2) using a follow-up question, 3) guiding to certain answer, 4) asking as provocation, 5) stating counter evidence, 6) using an information checking question, 7) using a short-question, 8) stating a request, and 9) using a hypothetical question. It including the use of the supportive questioning strategies in the interview discourse of the talk show, “Hone-Krasae”, to help Kanchai achieve the objectives of the interview as he wanted. The results revealed that the 6 support questioning strategies are: 1) teasing or joking, 2) cutting short the irrelevant, 3) repeating the answers, 4) showing support, 5) summarizing, and 6) expressing emotions or sympathy.